The shape of things to come - Wells, H. G. (Transworld, 2011)
Book the first : Today and tomorrow: the age of frustration dawns; Book the second : The days after tomorrow: the age of frustration; Book the third : The world renascence; the birth of the modern state; Book the fourth : the modern state militant; Book the fifth : the modern state in control of life